A scheme for passenger service-like backhaul for China railway express trains. (May 2022) - Du, Yiying; Zhou, Wenyuan; Lian, Feng
Abstract: Due to China's trade surplus with Europe, a significant imbalance exists between east- and westbound freight traffic on the China Railway Express (CR-Express). Many trains and containers return empty to China (i.e., empty backhaul), which leads to wasted freight capacity and significant economic loss. This paper presents an innovative, passenger service-like (PSL) mode, for improving the backhaul operations of CR-Express trains. The rationale for the proposed PSL CR-Express backhaul is verified through the multiple bilateral trade surpluses that exist along the CR-Express route, with which the corresponding container freight demand of each trade pair is estimated. A programming model is built to minimize the gap between the total costs of empty and PSL backhaul, and the freight revenue of PSL backhaul by determining the routes, stations visited, and cargo that needs handling for each train at each station. The numerical results show that, under the optimal scheme, the gap is −3.186 million USD/week for the balanced backhaul trains, and that 5148 FEU of cargo and 1662 FEU of empty containers will be transported in a week. Thus, we argue the proposed mode can more effectively utilize backhaul train capacity, which facilitates the sustainable growth of the CR-Express. Highlights: The multiple bilateral trade surpluses along the CR-Express route are calculated. Passenger service like (PSL) mode is suggested for CR-Express backhaul. Method for urban transit network design is adopted to optimize the PSL CR-Express backhaul network.